1996
DOI: 10.1073/pnas.93.9.4415
|View full text |Cite|
|
Sign up to set email alerts
|

Purification and characterization of a luminal cholecystokinin-releasing factor from rat intestinal secretion.

Abstract: Cholecystokinin (CCK) secretion in rats and humans is inhibited by pancreatic proteases and bile acids in the intestine. It has been hypothesized that the inhibition of CCK release caused by pancreatic proteases is due to proteolytic inactivation of a CCK-releasing peptide present in intestinal secretion. To purify the putative luminal CCK-releasing factor (LCRF), intestinal secretions were collected by perfusing a modified Thiry-Vella fistula of jejunum in conscious rats. From these secretions, the peptide wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 34 publications
2
54
0
Order By: Relevance
“…It has bee n ex plained tha t di eta ry proteins in th e intestin al lum en are recogni zed by th e feedbac k mechanism in the co ntrol of the exocrine pancrea ti c secreti o n. I S -17J In this mechanism, th e endogeno us CCK-releasing peptides (CCK-RP) but no t di etary proteins, ac t directly to intestina l epi thelia l cells. [18][19][20] Ho wever, specific recepto rs fo r the endogeno us CCK-RP have no t been identified yet. 21 -2 l) In contrast, we and other in vesti gators demonstrated th at pro teins were recogni zed in the intestin al lu men independent o f the feed back mechanism, and these repo rts indicate that pro teins could act d irectly to intestina l epi thelial cells incl uding CCK pro ducing enteroendocrin e cells .6.…”
Section: Discussionmentioning
confidence: 99%
“…It has bee n ex plained tha t di eta ry proteins in th e intestin al lum en are recogni zed by th e feedbac k mechanism in the co ntrol of the exocrine pancrea ti c secreti o n. I S -17J In this mechanism, th e endogeno us CCK-releasing peptides (CCK-RP) but no t di etary proteins, ac t directly to intestina l epi thelia l cells. [18][19][20] Ho wever, specific recepto rs fo r the endogeno us CCK-RP have no t been identified yet. 21 -2 l) In contrast, we and other in vesti gators demonstrated th at pro teins were recogni zed in the intestin al lu men independent o f the feed back mechanism, and these repo rts indicate that pro teins could act d irectly to intestina l epi thelial cells incl uding CCK pro ducing enteroendocrin e cells .6.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence has indicated that at least one mechanism causing CCK release involves endogenously produced releasing factors that are secreted into the lumen of the intestine and under the proper conditions to stimulate CCK secretion (Lu et al 1989;Miyasaka et al 1989;Spannagel et al 1996;Wang et al 2002). There is now strong evidence that a feedback mechanism exists in the chicken, pig, rat, dog and man.…”
Section: Factors Regulating Gastrin and Cholecystokinin Releasementioning
confidence: 99%
“…The hypothesis postulated that trypsin-sensitive intestinal-releasing factors were present in the small intestine lumen, and, when pancreatic proteases were absent, endogenously produced releasing factors are intact and would interact with the CCK cell to stimulate CCK release (79). This idea led to the discovery of luminal CCK-releasing factor (LCRF), isolated from rat intestinal washings (133), and diazepambinding inhibitor (DBI), isolated from porcine intestine (47). Both LCRF and DBI are involved in the negative feedback regulation of CCK secretion because they are intact and functional in the absence of the pancreatic proteases.…”
Section: Gut Cck-secreting Cellmentioning
confidence: 99%